Digital citizenship's ambiguity in cancel culture: from moral activism to cyberbullying - Sari, Yunita; Mulyono, Budi; Murdiono, Mukhamad; Suyato, Suyato (Jurnal Studi Komunikasi, 2026)
This study analysed critical discourse on digital citizens' comments regarding the Ridwan Kamil-Lisa Mariana case and interprets the concept of digital citizenship. This study used a qualitative approach with Fairclough's Critical Discourse Analysis (text, discourse practice, and socio-cultural practice). Data was collected using netnography techniques from 4,289 comments on the YouTube platform from six news and entertainment channels. The data was processed with NVivo 15 and visualised through matrix coding queries and word clouds. The results of the study show: 1. Critical discourse analysis on the text dimension shows that digital citizens' comments often use religious and moral diction such as ‘adultery’, ‘sin’, ‘mistress’, ‘cheap’, which function as labelling and symbolic punishment. The discourse practice dimension shows that comments easily spread following viral trends, so that emotional opinions are more quickly accepted than clarifications, resulting in moral activism turning into collective surveillance. The socio-cultural dimension is related to religious culture and social control in Indonesia, but in the digital space, these values have changed into mass pressure and digital vigilantism. 2. The shift from activism to bullying occurs due to virality, accompanied by negative labelling and religious undertones. Digital citizens tend to ignore four crucial elements related to digital citizenship, such as ethics, law, literacy, and rights and responsibilities. Therefore, these four elements need to be strengthened so that online participation does not turn into bullying.